Nitrogen Deposition Effects on Soil Properties, Microbial Abundance, and Litter Decomposition Across Three Shrublands Ecosystems From the Mediterranean Basin - Lo Cascio, Mauro; Morillas, Lourdes; Ochoa-Hueso, Raúl; Delgado-Baquerizo, Manuel; Munzi, Silvana; Roales, Javier; Spano, Donatella; Cruz, Cristina; Gallardo, Antonio; Manrique, Esteban; Pérez-Corona, María Esther; Dias, Teresa; et al. (Frontiers in Environmental Science, 2021)
Atmospheric nitrogen (N) inputs in the Mediterranean Basin are projected to increase due to fossil fuel combustion, fertilizer use, and the exacerbation of agricultural production processes. Although increasing N deposition is recognized as a major threat to ecosystem functioning, little is known about how local environmental conditions modulate ecosystem function response to N addition, particularly in the context of Mediterranean-Basin ecosystems. Here, we assess how N addition affects important ecosystem properties associated with litter decomposition, soil physical-chemical properties, soil extracellular enzymatic activity and microbial abundance across three long-term N addition experimental sites in the Mediterranean Basin. Sites were located in El Regajal (Madrid, Spain), Capo Caccia (Alghero, Italy), and Arrábida (Lisbon, Portugal) and are all representative of Mediterranean shrublands. No common pattern for litter decomposition process or other studied variables emerged among the control plots of the studied sites. Nitrogen supply only affected soil pH, a major driver of decomposition, in two out of three experimental sites. Moreover, when we explored the role of N addition and soil pH in controlling litter decay, we found that the effects of these factors were site-dependent. Our results point out to local ecosystem features modulating N addition effects in controlling litter decomposition rates in Mediterranean ecosystems, suggesting that the responses of soil functioning to N deposition are site-dependent. These findings provide further knowledge to understand contrasting ecosystem responses to N additions based on a single field experiments.